Hezberg’s theory of job satisfaction as predictor of job performance / Sarminah Samad - Samad, Sarminah (2004)
This paper presents the findings of a study, which investigated how perception of Hezberg’s two factor theory: motivational and hygiene factors played a significant role in employees’ job performance. A total of 584 staff from the managerial level in Telekom Malaysia (TM) were studied. The study used self administered questionnaire as the research instrument. The data obtained were then analyzed using correlation and regression analysis at .05 level of significance. The results hypothesized that both motivational and hygiene factors perceptions are positively related to job performance. Among all the facets, conducive working condition appeared to be the most significant predictor of job performance. The study reported both motivational and hygiene factors made significant contributions to employees’ job performance